Adsorpsi Fenol oleh Arang Aktif Ampas Kopi Teraktivasi Fisik dan Kimia - Nurfarizha, Harisma; Wirawan, Teguh; Widodo, Nanang Tri (JURNAL ATOMIK, 2021)
Activated charcoal was prepared from coffee grounds using carbonization at 500â°C as a physical activation and also by chemical activation using sulphuric acid. Chemical characterization of the activated charcoal was performed by Fourier Transform Infrared Spectroscopy. The optimum conditions for phenol adsorption was attained at pH 4 and 60 minutes of contact time. Adsorption isotherms from Freundlich